Gas equilibrium membrane inlet mass spectrometry (GE-MIMS) for water at high pressure - M. S. Brennwald; A. P. Rinaldi; J. Gisiger; A. Zappone; R. Kipfer; R. Kipfer (Geoscientific Instrumentation, Methods and Data Systems, 2024)
Gas species are widely used as natural or artificial tracers to study fluid dynamics in environmental and geological systems. The recently developed gas equilibrium membrane inlet mass spectrometry (GE-MIMS) method is most useful for accurate and autonomous on-site quantification of dissolved gases in aquatic systems. GE-MIMS works by pumping water through a gas equilibrator module containing a gas headspace, which is separated from the water by a gas-permeable membrane. The partial pressures of the gas species in the headspace equilibrate with the gas concentrations in the water according to Henry's Law and are quantified with a mass spectrometer optimized for low gas consumption (miniRUEDI or similar). However, the fragile membrane structures of the commonly used equilibrator modules break down at water pressures ≳3 bar. These modules are therefore not suitable for use in deep geological systems or other environments with high water pressures. To this end, the SysMoG® MD membrane module (Solexperts AG, Switzerland; “SOMM”) was developed to withstand water pressures of up to 100 bar. Compared to the conventionally used GE-MIMS equilibrator modules, the mechanically robust construction of the SOMM module entails slow and potentially incomplete gas–water equilibration. We tested the gas equilibration efficiency of the SOMM and developed an adapted protocol that allows correct operation of the SOMM for GE-MIMS analysis at high water pressures. This adapted SOMM GE-MIMS technique exhibits a very low gas consumption from the SOMM to maintain the gas–water equilibrium according to Henry's Law and provides the same analytical accuracy and precision as the conventional GE-MIMS technique. The analytical potential of the adapted SOMM GE-MIMS technique was demonstrated in a high-pressure fluid migration experiment in an underground rock laboratory. The new technique overcomes the pressure limitations of conventional gas equilibrators and thereby opens new opportunities for efficient and autonomous on-site quantification of dissolved gases in high-pressure environments, such as in research and monitoring of underground storage of CO2 and waste deposits or in the exploration of natural resources.